ANALISIS BIBLIOMETRIK: APPROACHING MATHEMATICS FOR SLOW LEARNERS BERBASIS VOS VIEWER - Atista Yasha; Hendra Kartika (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This research presents a bibliometric analysis of mathematical approaches for slow learners using the VOS Viewer analysis tool. Slow learners often encounter difficulties in understanding mathematical concepts, which are key components of the education curriculum. This study aims to explore trends, patterns, and research focus in this domain and to identify key contributors in the field. Bibliometric methods were employed to analyze a dataset consisting of indexed journals relevant to the chosen topic. The bibliometric method involved collecting journal data from 2019 to 2024 via Google Scholar using the Publish or Perish software, yielding 1,000 journals. Variables related to Approaching Mathematics for Slow Learners that have potential and novelty for future research include gamification, e-learning, critical thinking, student perception, student interest, machine learning, mathematical models, STEM, e-modules, digital literacy, science learning, blended learning, contextual teaching, mathematical formulations, artificial intelligence, scoping review, self-efficacy, intervention approaches, mathematics achievement, mathematical concepts, and action research.